Proposition of an attenuating solution for noise pollution caused by telecommunications installations and systems in urban environments - Zannin, Paulo Henrique Trombetta; Andrade, Erik de Lima (National Journal of City Management, 2021)
This study evaluates the noise generated by metallic cabinets of telecommunications transmission stations, before and after the implementation of a sound attenuator. The first step consisted of installing the attenuating system, which consisted of a glass wool plate on top of a metal cabinet. Then, we compared the results with a cabinet without the installation of the system. The speeds of the cooling system of the cabinets were the average and maximum. Noise measurements followed the guidelines of NBR 10151, and the acoustic descriptor used was the mean equivalent level (Leq). After verifying the effectiveness of the installation of the system in sound attenuation, several cabinets were adapted in installations located in two cities in southern Brazil. One installation was located in a residential area, with houses on its surroundings, and the other on top of a residential building. The study showed that the attenuating system was effective in reducing the noise generated by the cabinets, both at average and at maximum speed, in both locations. Although the final sound levels did not reach those recommended by the national standard NBR 10151, of acoustic comfort for communities, residents close to the facilities reported an improvement in the local acoustic environment.